Criteria for and Appropriateness of Renal Transplantation in Elderly Patients With End-Stage Renal Disease: A Literature Review and Position Statement on Behalf of the European Renal Association-European Dialysis and Transplant Association Descartes Working Group and European Renal Best Practice. Issue 10 (October 2016) - Segall, Liviu; Nistor, Ionuţ; Pascual, Julio; Mucsi, Istvan; Guirado, Lluis; Higgins, Robert; Van Laecke, Steven; Oberbauer, Rainer; Van Biesen, Wim; Abramowicz, Daniel; Gavrilovici, Cristina; Farrington, Ken; et al.
Abstract : Abstract: During the last 20 years, waiting lists for renal transplantation (RT) have grown significantly older. However, elderly patients (ie ≥65 years of age) are still more rarely referred or accepted to waiting lists and, if enlisted, have less chances of actually receiving a kidney allograft, than younger counterparts. In this review, we looked at evidence for the benefits and risks of RT in the elderly trying to answer the following questions: Should RT be advocated for elderly patients? What should be the criteria to accept elderly patients on the waiting list for RT? What strategies might be used to increase the rate of RT in waitlisted elderly candidates? For selected elderly patients, RT was shown to be superior to dialysis in terms of patient survival. Virtually all guidelines recommend that patients should not be deemed ineligible for RT based on age alone, although a short life expectancy generally might preclude RT. Concerning the assessment of comorbidities in the elderly, special attention should be paid to cardiac evaluation and screening for malignancy. Comorbidity scores and frailty assessment scales might help the decision making on eligibility. Psychosocial issues should also be evaluated. To overcome the scarcity of organ donors, elderly RT candidates should be encouraged to consider expanded criteria donors and living donors, as alternatives to deceased standard criteria donors. It has been demonstrated that expanded criteria donor RT in patients 60 years or older is associated with higher survival rates than remaining on dialysis, whereas living donor RT is superior to all other options. Abstract : This review discusses strategies to increase the access of elderly patients to kidney transplantation, from pretransplant careful evaluation, including cardiovascular, malignancy, frailty and psychological risks, to the use of expanded criteria donors and living donors, as alternatives to deceased standard criteria donors.